Alterações fisiológicas em milho cultivado em solo com alto teor de cobre e submetido à aplicação de zinco - Tiecher, Tadeu Luis (2014)
Due to the historical application of cupric fungicides in vineyards, the amounts of copper (Cu) in these soils can reach levels that cause toxicity to plants. Recently researchers have tried alternative products to the cupric ones, in order to reduce the amount of Cu applied to the vineyards, which usually shows zinc (Zn) in its composition. This study aimed to evaluate the biochemical and physiological changes in corn plants, grown in soil with a high content of Cu and different levels added of Zn. In November 2011 the soil was collected from the 0-15 cm layer of a vineyard with high Cu content and in an area of native grass adjacent to the vineyard, with low concentrations of Cu and Zn, which served as treatment control, and both soils were classified as Typic Hapludalf. The experiment was performed in a greenhouse and was divided into two corn crops, the first between March and April, and the second between October and November, both in 2012. The treatments were the doses of 0, 30, 60, 90, 180 and 270 mg kg-1 of Zn added to the soil of the vineyard, plus the control treatment. Treatments had pH values in water and levels of available phosphorus and exchangeable potassium similar. At 35 days after emergence the plants were harvested and the accumulation of dry matter from roots and shoots and the concentration of Cu and Zn in leaves were determined. It was also evaluated the operation of the photosynthetic apparatus from the fluorescence of chlorophyll a and the photosynthetic pigments, biochemical parameters related to oxidative stress in leaves of plants, such as activity of superoxide dismutase (SOD) and of non-specific peroxidase (POD) were evaluated. The high concentrations of Cu and Zn in soil caused toxicity to corn plants and provided foliar concentrations above the levels considered normal in the leaves, from both cultivations. The Zn toxicity was evidenced by the decrease in the growth of both roots and shoots, as well as the induction of symptoms of toxicity and deficiency in photosynthetic parameters, reflecting photoinhibition. Moreover, it was observed oxidative stress and the antioxidant system of maize plants was not effective enough to reverse the condition of stress, especially in cultivated soils received higher doses of Zn.